2017
DOI: 10.1080/10790268.2017.1294301
|View full text |Cite
|
Sign up to set email alerts
|

The Patient Health Questionnaire depression screener in spinal cord injury

Abstract: The PHQ-2 shows promise as a clinically useful screener in the community-residing SCI/D population. Findings regarding the presence of suicidal ideation emphasize the importance of routine screening for depressive symptomatology in the SCI/D population. Future research should investigate the role of the PHQ-2 in clinical decision-making and treatment monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 47 publications
0
2
0
1
Order By: Relevance
“…Regression analyses showed that marked social isolation, taking interferon, obesity, smoking, and low levels of exercise were associated with greater depression risk. Another 2018 study used PHQ-2 on 116 spinal cord injury/dysfunction (SCI/D) outpatients at Veterans Affairs Medical Center, and found that PHQ-2 showed promise as a clinically useful screener in the community-residing SCI/D population [19]. Our study used PHQ-2 to examine depression using the data of 8422 subjects taken from the Taiwan Biobank, and we also found both a significant relationship between smoking history and PHQ-2 and a clear indication that exercise, when examined with marital status, was significant to PHQ-2.…”
Section: Discussionmentioning
confidence: 99%
“…Regression analyses showed that marked social isolation, taking interferon, obesity, smoking, and low levels of exercise were associated with greater depression risk. Another 2018 study used PHQ-2 on 116 spinal cord injury/dysfunction (SCI/D) outpatients at Veterans Affairs Medical Center, and found that PHQ-2 showed promise as a clinically useful screener in the community-residing SCI/D population [19]. Our study used PHQ-2 to examine depression using the data of 8422 subjects taken from the Taiwan Biobank, and we also found both a significant relationship between smoking history and PHQ-2 and a clear indication that exercise, when examined with marital status, was significant to PHQ-2.…”
Section: Discussionmentioning
confidence: 99%
“…Depression is measured by the PHQ-2, which is a generic measure of depression. Among people with SCI, a cut-off score of 3 is associated with sensitivity of 83.3% and specificity of 95.7% 58…”
Section: Methods and Analysismentioning
confidence: 99%
“…Deste modo, é importante que existam medidas de autorrelato válidas para este tipo de população que não sejam longas e de fácil preenchimento. Na verdade, uma das principais barreiras para a triagem, diagnóstico e tratamentos eficazes e eficientes de perturbações depressivas é o facto de muitas das medidas utilizadas serem consideradas muito longas (ou seja, com mais de 20 itens) para serem úteis na prática de pesquisa populacional e, em particular, na rotina de acompanhamento na progressão clínica (Poritz et al, 2018).…”
Section: Introductionunclassified